2008
DOI: 10.1177/0269215508090161
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating the effect of a support and education programme for spouses of people affected by stroke

Abstract: Encouraging participation in the group meetings of a support programme might have a positive effect on psychological health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 18 publications
3
55
0
12
Order By: Relevance
“…[15,17,20,21] Our results also showed that the acquired knowledge was useful in daily life for both family members and the ill person. Duhamel and colleagues [20] also found that both the spouse and the ill person learned how to deal with the disease better.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…[15,17,20,21] Our results also showed that the acquired knowledge was useful in daily life for both family members and the ill person. Duhamel and colleagues [20] also found that both the spouse and the ill person learned how to deal with the disease better.…”
Section: Discussionsupporting
confidence: 65%
“…Earlier studies investigating the importance of education about disease-specific knowledge for family members has directed the education mostly to both the ill person and their family member, [14,15,20] but an educational programme for family members of stroke patients was directed only to the family members. [17,27] They did however not evaluate whether the participants would have preferred to have the education together with the person who had the stroke or not. The basic idea with the present programme was that it is important for family members to have the opportunity to express themselves and their experiences without the presence of the ill person, so that they could talk about their worries and discuss different issues openly and freely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On sekiz randomize kontrollü çalışmanın, dördünde SVH'lı hastaların sağlık bakım hizmetleri kullanımı azalmıştır. 22 Bakım 28 Uygulanan başka bir grup eğitiminde, bakım vericilere iletişim stratejileri, stres ve duygu yönetimi, gevşeme, iletişim hizmetlerine erişim ve koruyucu önlemlerin öğretimi yapılmıştır. Girişim sonrasında, iletişim becerileri açısından müdahale ve kontrol grubu arasında önemli bir fark belirlenmemiştir.…”
unclassified
“…Bakım vericileri geliştirme, güçlendirmeye yönelik bu girişimler maliyet etkili olduğu için uygulanabilir. 22,24,27,28,30,31,36 İnme öz yönetimini artırmak için yapılan bir çalışma, 10 hafta iki saatlik grup eğitimlerinden oluşmaktadır. Uygulanan öz yönetim programının en önemli sonuçlarından biri, bakım verenlerin topluma katılım oranındaki artıştır.…”
unclassified